Weber's Law and the Biological Evolution of Risk Preferences: The Selective Dominance of the Logarithmic Utility Function - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2002)
The paper offers a proof that expected utility maximisation with logarithmic utility is a dominant preference in the biological selection process in the sense that a population following any other preference for decision-making under risk will, with a probability that approaches certainty, disappear relative to the population following this preference as time goes to infinity. The result is contrasted with Weber's and Fechner's Psychophysical Law which implies logarithmic sensation functions for objective physical stimuli.
Keywords: 330; evolution; selection; risk preferences